Pengaruh Good Corporate Governance dan Ukuran Perusahaan Terhadap Kinerja Keuangan - Dame Ria Rananta Saragi; Lasma Lenida Rosinta Sianipar; Anita Tresia Samosir (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The aim of this research is to test and analyze the influence of good governance and company size on financial performance. The sample and population used in this research were 27 manufacturing companies listed on the IDX for the period 2020 - 2023. The sample was taken using a purposive sampling technique. The data analysis method in this research uses multiple linear regression analysis processed with SPSS 21 software. The results of this research prove that good corporate governance and company size have a positive effect on financial performance.